Predictors of mortality within three months in the patients with malignant pleural effusion - Ozyurtkan, Mehmet Oguzhan; Balci, Akin Eraslan; Cakmak, Muharrem (Elsevier Science Bv, 2010)
Background: Malignant pleural effusion (MPE) has a limited life expectancy (3-12 months). We investigated the predictors of the early mortality (EM) within three months. Methods: The patients were retrospectively grouped according to the death within three months (Group I) and survival more than three months (Group II). Demographical, clinical, and biochemical parameters in the fluid were analysed to determine their effects on the EM. The 30-day response rate of talc pleurodesis was investigated. Results: The study included 85 patients (Group I/Group II = 40/45). The patients in Group I died within a median of 28 days. Twenty-six patients in Group 11 died in a median of 205, but 19 were still alive (median 200 days). The median Survival was longer in renal cell, colorectal, breast, liver, ovarian and oropharynx carcinoma, and mesothelioma. Sixty-two patients (63%) underwent talc pleurodesis, which prevented the fluid reaccumulation (p = 0.04). The significant factors of the EM in the univariate analysis were the presence of high-risk tumors (lung, stomach, soft tissue, bladder, esophagus, prostate, cervix, and lymphoma), the low Karnofsky performance score (KPS) (p<0.0001), the low pH value of the fluid (p = 0.05), and the low concentration of glucose (p = 0.01), total protein (p<0.0001), and albumin (p<0.0001) in the fluid. According to the multivariate analysis high-risk tumors (p = 0.03), a lower KPS (p<0.001), and glucose value (p = 0.04) were the predictors of the EM. Conclusion: Talc pleurodesis prevents the fluid reaccumulation. High-risk tumors, a poor performance status, and lower pleural fluid glucose concentration are predictors of the EM within three months in the patients with a MPE. (C) 2009 European Federation of Internal Medicine. Published by Elsevier B.V. All rights reserved.
Keywords: Karnofsky performance score; Malignant pleural effusion; Mortality; Pleural disease; Pleural fluid biochemistry; Pleurodesis